2004
DOI: 10.1111/j.1945-5100.2004.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐calcium pyroxene as an indicator of igneous differentiation in asteroids and meteorites

Abstract: Abstract-Our analyses of high quality spectra of several S-type asteroids (17 Thetis, 847 Agnia, 808 Merxia, and members of the Agnia and Merxia families) reveal that they include both low-and highcalcium pyroxene with minor amounts of olivine (<20%). In addition, we find that these asteroids have ratios of high-calcium pyroxene to total pyroxene of >~0.4. High-calcium pyroxene is a spectrally detectable and petrologically important indicator of igneous history and may prove critical in future studies aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 57 publications
3
86
1
Order By: Relevance
“…If this were the case, the 2 μm band of our asteroid and meteorite spectra would resemble that of Vesta and eucrites, which is not the case. Thus, there is no evidence for partial melting on S-type surfaces, which is at odds with the conclusions of Sunshine et al (2004), Hardersen et al (2006), and Gietzen et al (2012).…”
Section: Compositional Analysis Of Our Meteorite and Asteroid Samplescontrasting
confidence: 46%
“…If this were the case, the 2 μm band of our asteroid and meteorite spectra would resemble that of Vesta and eucrites, which is not the case. Thus, there is no evidence for partial melting on S-type surfaces, which is at odds with the conclusions of Sunshine et al (2004), Hardersen et al (2006), and Gietzen et al (2012).…”
Section: Compositional Analysis Of Our Meteorite and Asteroid Samplescontrasting
confidence: 46%
“…Recent work found that Ibitira differed in Δ 17 O [30] and pyroxene Fe/Mn ratio [31] from other eucrites and may sample a separate parent body. Additional basaltic asteroids have also been identified [32], including 17 Thetis, whose average semimajor axis at 2.47 AU is close to the meteorite-delivering 3:1 resonance in the asteroid belt. While the link between eucrites and Vesta seems strong, we cannot rule out Ibitira and/or most eucrites originating on a body like Thetis.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the Cloutis et al (1986) regression was based on simple mixtures of olivine and orthopyroxene, the presence of more than one pyroxene (or other additional phases) would complicate spectral interpretations of asteroids made using this calibration (Gaffey et al, 1993;Sunshine et al, 2004).…”
Section: +mentioning
confidence: 99%